Chapter 25: Quantization of Light - Saifful Kamaluddin, Muzakir (SAP Publications Sdn. Bhd., 2011)
Max Planck started the revolution of quantum theory by challenging the classical physics and the classical wave theory of light. He proposed the concept of quantization of light to explain the black body radiation (which cannot be explained by the classical theories). Later, Einstein extended the concept to explain the observations in photoelectric effect experiment